Multiplexed azido‐group isotopic capture (MAGIC) beads: Selective analysis of azido compounds using a propargyl‐based cleavable linker, a proof of concept. (20th October 2016) - McLellan, Michelle; Doyle, Michael G. J.; Bodnar, Edward D.; Lopez, Paul G.; Domalaon, Ronald; Roy, Rini; Cordova, Katherine; Schweizer, Frank; Perreault, Hélène
Abstract : Rationale: A cleavable linker is designed and synthesized for the selective capture of azide‐containing compounds. This article presents a proof of concept methodology involving the use of peptide‐functionalized aminopropyl silica, on which the peptide is constructed by solid‐phase peptide synthesis. Methods: The peptide linker has L‐propargylglycine (Pra) at one terminal end to allow the conjugation of azide‐containing molecules by copper assisted azide alkyne cycloaddition, also known as click reaction. L‐Arginine (Arg) is placed just before Pra to permit the release of the captured product by tryptic cleavage. Three glycine (Gly) residues, as part of the linker, are appended to the silica bead to present a spacer section that allows efficient tryptic cleavage devoid of steric hindrance imposed by the bulky bead. The bead composition is Si‐O‐propyl‐NH‐Gly‐Gly‐Gly‐Arg‐Pra. Results: This solid‐phase material can be used to capture and release azide‐functionalized compounds. The beads are first tested on three azido compounds, 2‐azido‐2‐deoxyglucose (ADG), BOC‐ p ‐azido‐Phe‐OH (BAzPhe), where BOC =  tert ‐butoxycarbonyl, and tetraacetylated‐ N ‐azidomannosamine (Ac4 ManNAz). Copper‐mediated click reaction conditions are used and released products are characterized by matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF‐MS) and tandem MS (MS/MS). Conclusions: This method allows easy identification of captured compounds based on mass and fragmentation analysis. Moreover, it is useful for the analysis of small azide‐containing compounds by MALDI‐TOF‐MS which may not be possible otherwise due to matrix interferences. The insertion of isotopically labeled Arg residues provides the possibility of multiplex analysis, from which the beads have been called MAGIC (for Multiplexed Azido‐Group Isotopic Capture). Copyright © 2016 John Wiley & Sons, Ltd.